Récits d’Alceste : une approche (inter)textuelle - Bors, Edit (Romanica Silesiana)
This paper is concerned with the relationship between different texts dealing with misanthropy; more precisely, it examines the manifestations of rewritten forms of the story of Molière’s Alceste, by revealing the moral ambiguities inscribed in this character. The selected prose — Rousseau’s Rêveries du promeneur solitaire, Gide’s L’Immoraliste, Huysmans’s A rebours, Maupassant’s Un cas de divorce, Kafka’s Le terrier and Le départ — is the focus of this (inter)textual analysis concentrating on text-formatting tools that exhibit special narrative features in the structure of the discussed texts. It is argued that different manifestations of misanthropy — represented by the Natural Man, the Artificial Man and the Absurd Man — are closely connected with textual characteristics. Key words: Intertextuality, misanthropy, the Natural Man, the Artificial Man, the Absurd Man.